The effect of chronic disease health management on disease activity and renal injury in patients with lupus nephritis - Cheng-lin Zhong; Yi Liu; Li-hua Ni; Xiao-yan Wu (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To evaluate the effect of chronic disease health management on disease activity and renal injury in patients with lupus nephritis (LN). Methods A total of 97 LN patients diagnosed with lupus nephritis were randomizedly assigned to into two groups of chronic disease health management (n=49) and conventional management (n=48). and followed up for a median of 6 months. The disease activity index (SLEDAI), and blood and urinarye parameters and medicine compliance and living quality-of-life (SF-36) and trust in doctor physician were recordedobserved in at Month 6.Results Patients who managed by of chronic disease health management had lower disease activity compared to conventional group (P<0.05) and had better blood and urinarye parameters than conventional group (P<0.05)（chronic disease health management:red blood cells rise from（3.74±0.61）×1012/L to （4.37±0.58）×1012/L，albumin rise from(34.99±6.91)g/L to(39.82±4.59)g/L，creatinine drop from （63.66±26.18）μmol/L to （58.37±17.11）μmol/L，urea nitrogen rise from（5.03±1.95）mmol/L to （5.13±1.39）mmol/L，the number of hematuria cases decreased from 23 to 10, and the number of proteinuria cases decreased from 26 to 13 cases，conventional management red blood cells rise from （3.68±0.71）×1012/L to（4.07±0.65）×1012/L，albumin rise from（35.11±6.42）g/L to （36.76±7.54）g/L，creatinine rise from（60.66±18.06）μmol/L to （72.38±39.57）μmol/L，urea nitrogen rise from（5.03±1.94）mmol/L to （5.72±1.32）mmol/L，the number of cases of hematuria decreased from 24 to 19, and the number of cases of proteinuria decreased from 24 to 22（P<0.05）. And chronic disease health managed group was significantly higher than conventional group in terms of medication compliance, SF-36 scores and trust in doctor physician (P<0.05). Conclusions Chronic disease health management of LN patients may help reduced lower disease activity, in patients with lupus nephritis and improve renal injury, and increased theboost medication compliance and enhance and living quality-of-life and trust in physician.